Development of a Consensus Statement for the Definition, Diagnosis, and Treatment of Acute Exacerbations of Idiopathic Pulmonary Fibrosis Using the Delphi Technique. Issue 10 (October 2015) - Maher, Toby; Whyte, Moira; Hoyles, Rachel; Parfrey, Helen; Ochiai, Yuuki; Mathieson, Nicky; Turnbull, Alice; Williamson, Nicola; Bennett, Bryan
Abstract Introduction There is a lack of agreed and established guidelines for the treatment of acute exacerbations of idiopathic pulmonary fibrosis (AE-IPF). This reflects, in part, the limited evidence-base underpinning the management of AE-IPF. In the absence of high-quality evidence, the aim of this research was to develop a clinician-led consensus statement for the definition, diagnosis and treatment of AE-IPF. Methods A literature review was conducted to obtain published material on the definition and treatment of AE-IPF. The results of this review were circulated to an online panel of clinicians for review. Statements were then shared with ten expert respiratory clinicians who regularly treat patients with IPF. A Delphi technique was then used to develop a consensus statement for the definition, diagnosis and treatment of AE-IPF. During the first round of review, clinicians rated the clarity of each statement, the extent to which the statement should be included and provided comments. In two subsequent rounds of review, clinicians were provided with the group median inclusion rating for each statement, and any revised wording of statements to aid clarity. Clinicians were asked to repeat the clarity and inclusion ratings for the revised statements. Results The literature review, online panel discussion, and face-to-face meeting generated 65 statements covering the definition, diagnosis, and management of AE-IPF. Following three rounds of blind review, 90% of clinicians agreed 39 final statements. These final statements included a definition of AE-IPF, approach to diagnosis, and treatment options, specifically: supportive measures, use of anti-microbials, immunosuppressants, anti-coagulants, anti-fibrotic therapy, escalation, transplant management, and long-term management including discharge planning. Conclusion This clinician-led consensus statement establishes the 'best practice' for the management and treatment of AE-IPF based on current knowledge, evidence, and available treatments. Funding Boehringer Ingelheim Ltd., Bracknell, West Berkshire, UK.